EXPERIENCE OF RAILWAY TRANSPORT ENTERPRISES IN THE IMPLEMENTATION OF INNOVATIVE ACTIVITIES - D. Kregel (Вестник университета)
The experience of rail transport enterprises in the implementation of innovative activities was examined in the article. JSC «Russian Railways» is the main operator in the system of innovative activities in rail transport in Russia due to the monopolistic nature of the industry. The main scientific, technological and technological priorities of that holding for the long-term perspective (until 2025), the main examples of joint development of JSC «Russian Railways» and Russian enterprises that surpass the best foreign models, as well as the main problems which impede the implementation strategies of innovation development are considered.